Peningkatan hasil belajar matematika dengan menggunakan alat peraga pada siswa kelas VI SD Negeri 018 Rambah Hilir - Herlina, Eli (Jurnal Pendidik Indonesia, 2020)
During the mathematics learning process, students were less active and struggled to understand mathematical concepts, as seen from their learning outcomes, which were often average or below average. Therefore, appropriate instructional improvements, such as the use of teaching aids, are necessary. This study aims to improve mathematics learning outcomes through the use of teaching aids for sixth-grade students at SD Negeri 018 Rambah Hilir. The subjects of this study were 24 sixth-grade students at SD Negeri 018 Rambah Hilir, consisting of 10 boys and 14 girls. This research is a classroom action research (CAR). The procedure included planning, implementation, observation, and reflection. The research instruments included learning materials and data collection tools. The results showed that the students' absorption rate in cycle I, meeting 1 was 72.70 (Poor) and in cycle I, meeting 2 was 76.45 (Fair), resulting in an average of 74.6 for cycle I. In cycle II, meeting 1, the absorption rate was 79.58 (Fair) and in cycle II, meeting 2, it was 84.37 (Good), resulting in an average of 82.0 for cycle II. The classical learning completeness was not achieved in cycle I (23.00%) but was achieved in cycle II (100.00%). Thus, the use of teaching aids can improve mathematics learning outcomes for sixth-grade students at SD Negeri 018 Rambah Hilir.